IMPLEMENTATION OF SPMI (INTERNAL QUALITY ASSURANCE SYSTEM) IN HIGHER EDUCATION AS AN EFFORT TO IMPROVE THE QUALITY OF HIGHER EDUCATION - Asma, Fery Rahmawan; Akrom, Muhammad; Irawan, Ari (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2025)
This study aims to evaluate the effectiveness of the implementation of the Internal Quality Assurance System (SPMI) and External Quality Assurance System (SPME) in higher education environments, and the extent to which its implementation is in line with the National Higher Education Standards (SN-DIKTI). The research method used is descriptive qualitative, with an observational and descriptive approach to the quality process and policies at the study program and institutional levels. The results of the study show that many universities implement SPMI as part of their preparation for external accreditation (SPME) by BAN-PT or LAM. However, after obtaining accreditation, the implementation of internal quality evaluation activities such as Internal Quality Evaluation (EMI) and Internal Quality Audit (AMI) are often delayed or even ignored. This finding indicates a gap between the technical implementation of SPMI and its main objective, namely sustainable quality culture. Therefore, a commitment from higher education institutions is needed to build a systematic and consistent quality culture as part of good governance and continuous improvement of the quality of academic and non-academic services.